Analisis Kritis atas Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan terhadap Pelaksanaan Poligami - Hijrah Lahaling (Al-Mizan (e-Journal), 2021)
In principle, in a marriage a man can only have one wife. A wife can only have one husband. However, in the marriage law, there are opportunities for polygamy, where the Court can give permission to a husband to have more than one wife if the parties concerned want. based on an agreement between the parties concerned, such as the previous wife. This article will discuss the implementation of Law No. 1 of 1974 concerning the implementation of polygamy. The method used is the juridical normative which is analyzed by qualitative descriptive. The results showed that the implementation of Law No. 1 of 1974 concerning the implementation of polygamy still have weaknesses, because some articles in the law is very ambivalent. In addition, the Act does not have an article that regulates the legal sanctions against those who violate the regulations governing the implementation of polygamy, but the existence of legal sanctions in the Act is absolutely necessary to guarantee the rights of citizens.